(untitled) (Research, Society and Development, 2021)
Introduction: confront with viral hepatitis has been a major challenge, especially for countries with high prevalence and social vulnerabilities that make access to care difficult. Objective: To investigate the national scientific production on strategies for prevention, control and treatment of viral hepatitis. Methodology: it is an integrative review operationalized through consultation with the bases/libraries: Nursing Database (BDENF), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and National Library of Medicine National Institutes of Health (PubMed) via MEDLINE, from January 1998 to December 2019.The main question was: With regard to HV in humans, what are the strategies performed by health services for control, treatment and prevention, described in national quantitative studies published from January 1998 to December 2019? The PRISMA flowchart was used to select the articles. Results: we found 2722 empirical articles, 26 of which met the selection criteria, and were grouped into the following categories: I. Treatment - 84.6% (22) and II. Prevention and Control - 15,3% (4).The treatment of Hepatitis C (86.3%) with use of Interferons with or without Ribavirin and the main adverse effects are headache, anemia and fatigue. Conclusion: there has been evidence in the national literature of a broader approach to treatment, especially of Hepatitis C, and a lack of studies on prevention and control strategies for viral hepatitis, which denotes the relevance of expanding publications systematizing the effective intervention plans that health services perform.